Effect of Storage Methods and Periods on the Nutritional Properties of Watermelon (Texas Journal of Agriculture and Biological Sciences, 2022)
the article presents the results of research on changes in fruit quality and chemical composition when fruits of watermelon varieties and hybrids are stored in a combined method (in the open field and in a naturally ventilated warehouse). Also in the article, the advantages of this storage method are explained from a scientific point of view.